VARIATIONS IN IMMUNE FATIGUE AND PHYSICAL PERFORMANCE AMONG AMATEUR SOCCER PLAYERS DURING FASTING - Fenni , Yakoub; Ikiouane , Mourad; Kettab , Khaled; Zaabar , Salim; Rouabi, Sif Eddine; Chafa, Ameur (Physical Education and Sport Through The Centuries, 2025)
This study examines the impact of Ramadan fasting on immune fatigue and physical performance in amateur soccer players. Ten male players (22.8 ± 3.5 years) from the Wilaya of Bejaia participated in this longitudinal study. Creatine Phosphokinase (CPK) and C-Reactive Protein (CRP) were assessed as markers of muscle damage and systemic inflammation. Explosive muscle power was evaluated using Squat Jump (SJ) and Countermovement Jump (CMJ) tests. Data were collected before, during, and after Ramadan. CRP levels significantly decreased during fasting (p = 0.000, effect size = 0.75), suggesting anti-inflammatory effects. However, CPK levels showed no significant changes (p = 0.279, effect size = 0.35), indicating minimal muscle damage. SJ (p = 0.937, effect size = 0.12) and CMJ (p = 0.426, effect size = 0.22) performances remained stable, suggesting fasting did not impair explosive muscle power. These findings highlight Ramadan fasting’s potential immune benefits without compromising performance, given proper training and nutrition. Future studies should examine training intensity, dietary habits, and compare amateur with professional athletes to better understand physiological adaptations. Larger sample sizes are recommended to improve generalizability.